Influence of structure, pH and membrane potential on proton movement in cytochrome oxidase - Mills, Denise A; Ferguson-Miller, Shelagh (Biochimica et biophysica acta, 2002)
Cytochrome c oxidase (C cO) reconstituted into phospholipid vesicles and subject to a membrane potential, exhibits different characteristics than the free enzyme, with respect to effects of mutations, pH, inhibitors, and native structural differences between C cO from different species. The results indicate that the membrane potential influences the conformation of C cO and the direction of proton movement in the exit path. The importance of the protein structure above the hemes in proton exit, back leak and respiratory control is discussed.